Financial Shocks and the Erosion of Interpersonal Trust: Evidence from Longitudinal Data - Michael Jetter; Ingebjørg Kristoffersen (Institute of Labor Economics (IZA), 2017)
This paper evaluates the effect of financial shocks on interpersonal trust levels, exploiting longitudinal survey data from 22,112 Australians. Using within-individual level variation, we find that trust does not change meaningfully following a positive financial shock (e.g., winning the lottery). However, trust falls sharply following a negative financial shock (e.g., bankruptcy). In terms of magnitude, this effect is approximately equivalent to the effect observed after one reports being the victim of physical violence or a property crime, but significantly larger than effects from a range of other individual-level shocks (e.g., being fired or getting divorced). We then explore a potential explanation of this finding related to locus of control, which relates to the extent to which people believe they are in control of their circumstances. Indeed, we find evidence consistent with this hypothesis as locus of control tends to change, and become less internal, following a negative financial shock. In turn, locus of control is closely associated with interpersonal trust levels.
Keywords: D90; E32; G40; Z1; 330; financial shocks; trust levels; locus of control